2021
DOI: 10.3390/polym13101643
|View full text |Cite
|
Sign up to set email alerts
|

On the Effectiveness of Oxygen Plasma and Alkali Surface Treatments to Modify the Properties of Polylactic Acid Scaffolds

Abstract: Surface modification of 3D-printed PLA structures is a major issue in terms of increasing the biofunctionality and expanding the tissue engineering applications of these parts. In this paper, different exposure times were used for low-pressure oxygen plasma applied to PLA 3D-printed scaffolds. Alkali surface treatments were also evaluated, aiming to compare the modifications introduced on the surface properties by each strategy. Surface-treated samples were characterized through the quantification of carboxyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Our study demonstrated that the water and diiodomethane contact angles on PLGA films were significantly reduced after the plasma treatment. These results are consistent with previously reported studies on an oxygen plasma treatment of poly(lactic acid) (PLA) scaffolds [ 42 , 55 ] and PLGA films [ 56 ]. The wettability of PLGA-based biomaterials has been reported to be a function of the lactide/glycolide ratio, and the wettability can be enhanced after plasma treatments [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrated that the water and diiodomethane contact angles on PLGA films were significantly reduced after the plasma treatment. These results are consistent with previously reported studies on an oxygen plasma treatment of poly(lactic acid) (PLA) scaffolds [ 42 , 55 ] and PLGA films [ 56 ]. The wettability of PLGA-based biomaterials has been reported to be a function of the lactide/glycolide ratio, and the wettability can be enhanced after plasma treatments [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has been generally accepted that plasma surface modifications can improve the surface wettability [ 42 , 43 , 44 , 45 ] and cellular attachment [ 15 , 16 , 46 , 47 , 48 , 49 , 50 ] of polymeric scaffolds. A plasma surface treatment can be advantageous in supporting cell adhesion due to the added functionality on the cell–biomaterial interface in their early regeneration phase [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent treatment with citric acid improved surface hydrophilicity and introduced porosity . In another comparison between oxygen plasma-treated and wet chemical-treated 3D scaffolds of PLA, it was found that chemical etching generates a higher number of surface functional groups (carboxylic acid) and higher porosity than the plasma-treated scaffolds . The etching parameters can be easily varied by changing the temperature, type, and concentration of the alkali/acid, etc.…”
Section: Surface and Bulk Functionalization For Tissue Engineering Ap...mentioning
confidence: 99%
“…Because these methods only affect the surface’s physical state and do not alter the bulk scaffold’s chemical composition, they are highly translatable across various types of scaffolds . The topographical modifications of several hard polymeric scaffolds such as PLA, PLGA, PCL, and polystyrene have been reported . These modifications are largely restricted to a few microns or nanometers from the scaffold surface.…”
Section: Surface and Bulk Functionalization For Tissue Engineering Ap...mentioning
confidence: 99%
See 1 more Smart Citation